Chinese Path to Modernization: An Analysis of the Similarities and Differences in the Modernization of World Civilizations - Chen, Huanshen (International Journal of Social Sciences and Public Administration, 2024)
Since the mid-18th century, when the West began its modernization, countries around the world have progressively engaged in their own modernization processes, influenced by this historical trend. After more than 250 years of exploration and adaptation, Western nations have largely completed their modernization. In contrast, many non-Western countries, hindered by colonial oppression and the disintegration of their existing economic structures, have hastily sought solutions by blindly adopting the Western development model, resulting in significant social unrest. This situation serves as a reminder for China that, in the process of modernization, it must carefully analyze specific challenges based on its own national conditions while drawing on both the successful and failed experiences of modernization from other countries. Consequently, China's path to modernization should embody the common characteristics of modernization shared by all nations while also reflecting the unique aspects of its own national context. The purpose of this study is to summarize the common features, as well as the respective advantages and disadvantages, of the modernization paths of the world's major civilized regions, with the aim of providing valuable insights for China's modernization journey. This paper will employ desk research methods to gather information from various media sources and analyze the Chinese path to modernization accordingly.